2008
DOI: 10.1115/1.2912722
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solutions for the Modeled k Equation

Abstract: The semitheoretical function of Nezu and Nakagawa (1993, Turbulence in Open-Channel Flows, A. A. Balkema, ed., Rotterdam, The Netherlands) for the turbulent kinetic energy k is valid only where local equilibrium is a good approximation. From an estimation of the difference between the energy production and its dissipation G−ϵ, we present in this study an analytical solution for the modeled k equation. Comparisons with direct numerical simulation data of turbulent channel flows show good agreement. A universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…As it was mentioned before, in the numerical calculations the turbulence model k-was applied. Turbulence kinetic energy (TKE) can be generated by fluid shear, friction or buoyancy, or through an external force at low-frequency eddy scales [1]. Analysing in Figure 8 the distributions of Turbulent Kinetic Energy (TKE) through the Venturi mixer for different gas inlet angles it could be seen how the TKE is growing up through the Venturi throat.…”
Section: Resultsmentioning
confidence: 99%
“…As it was mentioned before, in the numerical calculations the turbulence model k-was applied. Turbulence kinetic energy (TKE) can be generated by fluid shear, friction or buoyancy, or through an external force at low-frequency eddy scales [1]. Analysing in Figure 8 the distributions of Turbulent Kinetic Energy (TKE) through the Venturi mixer for different gas inlet angles it could be seen how the TKE is growing up through the Venturi throat.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, from the modeled k-equation, we developed a function for k + for y + < 20 [4]. For steady channel flows, we write the k-equation as ∂ y (ν t ∂ y k) = − (G + ∂ y (ν ∂ y k) − ), where G and are respectively the energy production and dissipation.…”
Section: B a Near-wall Eddy Viscosity Formulationmentioning
confidence: 99%
“…For steady channel flows, we write the k-equation as ∂ y (ν t ∂ y k) = − (G + ∂ y (ν ∂ y k) − ), where G and are respectively the energy production and dissipation. With an approximation for the right-hand side as (G + d y (ν d y k) − ) ≈ 1/y 2 and by integrating, we obtained [4] k + = B y +2C e (−y + /A + k ) [4]. We write therefore k + for y + ≤ 20 as…”
Section: B a Near-wall Eddy Viscosity Formulationmentioning
confidence: 99%
“…This parabolic profile was not proposed by Yang et al [2] as indicated by the authors, but was proposed some decades ago (see Yalin [3, p. 202], and Nezu and Nakagawa [4, p. 66], as indicated by Yang et al [2]). The discusser indicates that it is possible to write a more accurate eddy viscosity based on an analytical solution for the turbulent kinetic energy [5] with a suitable mixing length equation.…”
mentioning
confidence: 99%